Decision making process practised at planning phase in Malaysia / Nurul Atiqah Mohd Sofberi and Rozlin Zainal - Mohd Sofberi, Nurul Atiqah; Zainal, Rozlin (Universiti Teknologi MARA, Perak, 2020)
This study examines the decision making process practised by Malaysian housing developers at the planning phase for housing development. The theoretical process model is developed by integrating the process that has been established by numerous authors and researchers on the subject of decision making. Sets of the questionnaire are distributed to private housing developers and analysed using Statistical Package for Social Sciences (SPSS). Hence, this study provides a new process model for decision making at the planning phase of housing development in Malaysia and helps developers and governments to make better predictions before proceeding to the construction phase.